Meningkatkan Hasil Belajar Siswa dengan Implementasi Model Learning Cycle 7E Berbantuan Media Video - Arham, Immawan (Jurnal Teladan: Jurnal Ilmu Pendidikan dan Pembelajaran, 2022)
The problems that arise in class XII TPm 2 SMK Negeri 1 Tuban, in the implementation of Produk Kreatif dan Kewirausahaan (PKK) learning ultimately have an impact on decreasing student learning outcomes of XII TPm 2. For this reason, the problems that occur in class XII TPm 2 must be resolved immediately. The implementation of the 7E Learning Cycle Model Assisted by Video Media is a solution to improve the learning outcomes of class XII TPm 2 SMK Negeri 1 Tuban students in the subject of Produk Kreatif dan Kewirausahaan (PKK). This research was started by conducting learning with conventional models at the pre-cycle stage, and as a result, there were only 14 (38.89%) students who achieved the minimum criteria for passing the predetermined test, with an average score of 67.14. After the implementation of the Learning Cycle 7E Model Assisted by Video Media, there was an increase in the learning outcomes of class XII TPm 2 students. class XII TPm 2 who reached the minimum completeness criteria, with an average score of 81.00. While in the second cycle there were 34 (94.44%) students who achieved the minimum completeness criteria, with an average score of 84.44. Based on the data analysis results, it can be stated that the learning outcomes of class XII TPm2 students in the subjects of Produk Kreatif dan Kewirausahaan (PKK), have increased, to exceed the indicators of research success that have been set. This shows that the application of the 7e learning cycle model assisted by video media has succeeded in improving the learning outcomes of class XII TPm 2 students.